2017
DOI: 10.1094/cchem-10-16-0251-r
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Different Varieties of Quinoa

Abstract: Cereal Chem. 94(5):847-856Quinoa is a pseudocereal from South America known for its unique nutritional properties. Hundreds of varieties and experimental lines are currently either grown or in development in many countries around the world. There exists a lack of information about, and understanding of, the nutritional composition and processing characteristics of these varieties and their potential end-use applications. Twenty-eight quinoa varieties and experimental lines tested in the Washington State Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 66 publications
10
56
3
2
Order By: Relevance
“…The variability found in this study was higher than that reported by Aluwi et al. () and Vidueiros et al. (), and fitted within the range of values reported by Miranda et al.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The variability found in this study was higher than that reported by Aluwi et al. () and Vidueiros et al. (), and fitted within the range of values reported by Miranda et al.…”
Section: Resultssupporting
confidence: 90%
“…The mean carbohydrates content was higher than values reported for Chilean genotypes (Aluwi et al., ; Miranda et al., ) and generally coborrate previous reports from Andean cultivars (Aluwi et al., ). In contrast to Miranda et al.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Quinoa ( Chenopodium quinoa Willd.) is an ancient seed crop from the Andean region, and in the last 30 years, it has gained considerable attention worldwide due to its nutritional and health benefits, as well as its flavourful and high‐quality seeds (Aluwi, Murphy, & Ganjyal, ; Kowalski, Medina‐Meza, Thapa, Murphy, & Ganjyal, ; Wu, Morris, & Murphy, , ; Wu, Ross, Morris, & Murphy, ). Most notably, it is prized for its well‐balanced complement of amino acids and high mineral concentration of iron, calcium and phosphorus (González, Konishi, Bruno, Valoy, & Prado, ; Navruz‐Varli & Sanlier, ; Vega‐Gálvez et al., ; Wu, ; Wu, Peterson, Morris, & Murphy, ).…”
Section: Introductionmentioning
confidence: 99%